The platform executive: Technology shaping of executive cognition during digital service innovation - Wiredu, G.O.; Boateng, K.A.; Effah, J.K. (Information & Management, 2021)
The upsurge of digital innovations around the world has led to the establishment of many digital organizations, mostly small-medium, that focus on digital service innovation. For such organizations, the dominant use of digital technologies significantly shapes the cognition of their executives. But technology shaping of executive cognition is underresearched and, hence, underexplained. This paper seeks to address this limitation through an empirical study informed by critical realism and media ecology theory. The study explains how and why digital technology shapes executive cognition through combined influence of digital platforms and applications, service innovation, and executive functions. This explanation leads to the conceptualization of the executive of the digital organization as a platform. The Platform Executive is characterized by cognitive restructuring in a rapid and innovative manner during engagement with digital technologies. Based on these explanations, the paper discusses the theoretical, research, and practical implications.
Research Article
Keywords: Digital; Platform; Executive